MOURNING AND THE MOVIE SPIRITS’ HOMECOMING - JO, Seyon (International Journal of Korean Humanities and Social Sciences, 2017)
The movie Spirits’ Homecoming connects the past and the present through two Korean “comfort women” and reveals their life, anguish and mourning. Based on Derrida’s concept of mourning, this paper analyzes mourning of the main characters and the movie. Furthermore, it focuses on how Korean viewers reacted through mourning presented in Spirits’ Homecoming. By doing so, this paper criticizes how the film’s vivid representation of “comfort women” reflects patriarchal and nationalist ideologies which position the “comfort women” as the ultimate victims in Korean society.